PENGARUH PERSONAL SELLING AGEN PENJUALAN TERHADAP BRAND IMAGE MOBIL TOYOTA ETIOS - Putra, Candra; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted at PT Agung Automall Pekanbaru in order todetermine the influence of personal selling sales agent for Toyota Etios BrandImage PT Agung Automall Pekanbaru. Variable in this research are: personalselling and brand image. The sample in this study is as much as 94 consumersusing proportional random sampling technique. The analytical method used issimple regression. Based on the results obtained between the influences ofPersonal Selling Sales Agent Against Brand Image by using the coefficient ofdetermination is KD = r 2 x 100% = (0732) 2 x 100% = 0536 means that theaverage value amounting to 53.6% of brand image are determined by PersonalSelling Dealers. Furthermore, from the results obtained regression equation Y =12 236 + 0242 X. The equation shows that if the Personal Selling Agent Salesincreased by 1 unit will affect the brand image of the increase in 0242, as seenfrom the value of b is positive. Results of hypothesis testing t = 6937> t table =2.000 at 95% confidence level. Based on these results that there is influencebetween Personal Selling Sales Agent Against Brand Image Toyota Etios(Business Case PT Agung Automall Car Sales Pekanbaru)Keywords: Personal Selling, brand image